The Efficacy and Safety of Liquid-Type Botulinum Toxin Type A for the Management of Moderate to Severe Glabellar Frown Lines. Issue 3 (March 2015) - Kim, Jung Eun; Song, Eun Jong; Choi, Gwang Seong; Lew, Bark-Lynn; Sim, Woo-Young; Kang, Hoon
Abstract : Background: Botulinum toxin type A has been widely used to correct unwanted hyperfunctional facial lines. Most forms of botulinum toxin type A currently used require reconstitution, which is very inconvenient for users. The authors compared the efficacy and safety of a newly developed liquid-type botulinum toxin type A (MT10109L) and onabotulinumtoxinA (Botox) for moderate to severe glabellar lines. Methods: A double-blind, randomized, active drug–controlled, phase III study with 168 enrolled subjects was performed. The primary efficacy endpoint was the improvement rate at maximum frown at week 4 by the investigators' live assessment. The secondary efficacy endpoint included the improvement rate at maximum frown at week 16 and at rest at weeks 4 and 16 by live assessment, and the improvement rate at maximum frown and at rest based on photographic assessment at week 4. Self-assessment and self-satisfaction with glabellar line improvement were also evaluated. Results: The improvement rate at maximum frown by live assessment was not significantly different between the MT10109L and Botox groups. In addition, the improvement rate of glabellar lines at rest based on the investigators' live assessment and photographic assessment was similar in both treatment groups. However, the improvement rate at maximum frown by live assessment at week 16 was significantly higher in the MT10109L group compared with the Botox group. There were no severe adverse events. Conclusions: The efficacy and safety of MT10109L were comparable to those of Botox for the management of glabellar frown lines. MT10109L provides greater convenience because it does not require dilution and has long-lasting effects. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.